Understanding the role of traditional healers in the HIV care cascade: Findings from a qualitative study among stakeholders in Mwanza, Tanzania. - Dunstan J Matungwa; Richie Hong; Jeremiah Kidola; Daniel Pungu; Matthew Ponticiello; Robert Peck; Radhika Sundararajan (Public Library of Science (PLoS), 2022)
Tanzania is HIV-endemic, with 5% prevalence. However, less than half of Tanzanians are aware of their HIV status, and only 75% of adult Tanzanians living with HIV are on antiretroviral therapy (ART). Informal healthcare providers, such as traditional healers, frequently serve as the first line of healthcare in Tanzania. How traditional healers interact with people living with HIV (PLWH) remains unknown. This study sought to understand gaps in HIV care and explore how traditional healers interface with PLWH along the HIV care cascade. We conducted a qualitative study in Mwanza, Tanzania, between November 2019 and May 2020. We invited 15 traditional healers, 15 clients of traditional healers, 15 biomedical healthcare facility staff, and 15 PLWH to participate in a single qualitative interview. Two community focus groups were held with eight male and eight female participants. Participants were 18 years of age or older. Individual experiences with traditional healers and biomedical healthcare facilities, as well as perceptions of traditional healers with respect to HIV care, were explored through interviews. Using a content-analysis approach, codes were grouped into a framework that characterized how traditional healers engage with PLWH throughout the HIV care cascade. PLWH engaged with traditional healers throughout the HIV care cascade, from pre- to post-HIV diagnosis. Traditional healers were described in some cases as facilitating HIV testing, while others were described as delaying testing by providing traditional treatments for HIV symptoms. Traditional medications were frequently used concurrently with ARTs by PLWH. There was concern that healers contributed to ART nonadherence as some PLWH used traditional therapies in search of a "cure" for HIV. Our findings suggest that traditional healers interact with PLWH throughout the HIV care continuum and that collaboration between traditional healers and biomedical healthcare professionals and facilities is needed to improve HIV treatment outcomes.